Validation of a Single Question Health Literacy Screening Tool for Older Adults. (6th June 2017) - Keene Woods, Nikki; Chesser, Amy K.
Objectives: Health Literacy skills are important for people of all ages. Older adults have the lowest health literacy rates. The purpose of this study was to assess health literacy rates and validate the use of a screening tool with older adults.Methods: Participants included a convenience sample, age 65 years or older, English speaking with corrected vision of 20/100 or better and typical cognitive skills. Participants completed the 36-item Short Test of Functional Health Literacy Assessment (STOFHLA) and a single item screening (SIS) tool. Results of STOFHLA and SIS were compared using nonparametric statistics.Results: Of the 64 participants, 94% had adequate scores on the STOFHLA, while 64% self-reported confidence in filling out medical forms, p = .006, χ 2 = 7.606, df (1).Conclusion: Results suggest that use of health literacy screening tools for older adults may be of value. Additional studies are needed to expand the study sample and validate the findings of this study.